2021
DOI: 10.3390/ijerph181910545
|View full text |Cite
|
Sign up to set email alerts
|

The Effectiveness of Disaster Education for Undergraduate Nursing Students’ Knowledge, Willingness, and Perceived Ability: An Evaluation Study

Abstract: As future healthcare professionals, nursing students should possess the appropriate knowledge, skills, and positive attitude to respond to public health emergencies or disasters worldwide. This study evaluated the effectiveness of a disaster management training course at improving Hong Kong nursing students’ disaster knowledge, willingness, and perceived ability. A mixed-method design using a single group with pre- and post-intervention comparisons followed by qualitative focus group interviews, was conducted.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
18
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 50 publications
0
18
0
1
Order By: Relevance
“…Practical disaster management training is essential and beneficial to prepare disaster nursing competencies [ 64 ]. It could enhance future nurses’ knowledge and skills in coping with public health emergencies and disasters [ 64 , 65 , 66 ]. Although there is in-service and postgraduate disaster nursing training locally, disaster preparedness training has not been adequately included in the curriculum of undergraduate general nursing training [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Practical disaster management training is essential and beneficial to prepare disaster nursing competencies [ 64 ]. It could enhance future nurses’ knowledge and skills in coping with public health emergencies and disasters [ 64 , 65 , 66 ]. Although there is in-service and postgraduate disaster nursing training locally, disaster preparedness training has not been adequately included in the curriculum of undergraduate general nursing training [ 67 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although there is in-service and postgraduate disaster nursing training locally, disaster preparedness training has not been adequately included in the curriculum of undergraduate general nursing training [ 67 ]. Evidence shows that simulated disaster education with blended learning activities effectively prepares nursing students’ and improves their confidence in responding to disasters [ 65 , 66 , 68 , 69 ]. Therefore, to develop and strengthen future nursing professionals’ disaster competencies, faculties of universities are suggested to integrate more public health emergency and disaster education into the curricula of basic nursing programs.…”
Section: Discussionmentioning
confidence: 99%
“…In Hung et al's study, before intervention students knowledge and perceived ability were poor, and they don't have willingness to respond to disasters. 18 Furthermore, nursing students participating in the study by Yan et al found that there is a gap between their knowledge and their ability to participate in disaster situations. 24 However, in Kim et al's study, the average level of disaster competency of nursing students was 2.76 out of 5, which was reported as average, and the mean score of readiness among participants was 2.14 out of 14 points.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that most nurses and nursing students lack the competencies required for nursing in disaster situations. [16][17][18] Nurses' inability to play their role effectively in providing care to those affected by disaster can lead to missed care and poor(er) health outcomes for victims. 19,20 Problems that impede medical response arise from the inadequate education and training of health care professionals, as well as skill inadequacy and lack of experience.…”
mentioning
confidence: 99%
“…Even if they are sufficiently capable, nurses that are unwilling to work are likely to unable to efficiently response a disaster which shows the importance of determining the willingness and competence of nurses [17]. Despite the existence of studies that consider willingness and competence of nurses together [18,19,20,21], there is a need for these considerations to be made for a wider scale. Additionally, no study was found in Turkey that tackles these considerations.…”
Section: Introductionmentioning
confidence: 99%